2011
DOI: 10.1080/00036846.2010.498358
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of a new product under network effects: the US DVD market

Abstract: We formulate a model that captures the inter-dependence between hardware demand and software supply - indirect network effect - in the DVD industry. The identification of the network effect comes from the difference in software availability across two different formats: VHS and DVD. We find that a 1% increase in the number of DVD titles raises the demand for DVD players by 0.87%. Simultaneously, a 1% increase in video player ownership leads to a 0.14% increase in the variety of video titles. Our simulations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…First, empirical research on system markets has focused on detecting the indirect network effects of various entertainment products, including DVDs (Inceoglu & Park, 2011), computer hardware and software (Frels, Shervani, & Srivastava, 2003), CDs (Basu, Mazumdar, & Raj, 2003), VCRs (Park, 2004), and home video games (Chintagunta, Nair, & Sukumar, 2009). To date, direct network effects have been rarely considered (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First, empirical research on system markets has focused on detecting the indirect network effects of various entertainment products, including DVDs (Inceoglu & Park, 2011), computer hardware and software (Frels, Shervani, & Srivastava, 2003), CDs (Basu, Mazumdar, & Raj, 2003), VCRs (Park, 2004), and home video games (Chintagunta, Nair, & Sukumar, 2009). To date, direct network effects have been rarely considered (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have criticized earlier research that examined demand-side effects without controlling for the endogeneity of title availability (e.g., Dubé, Hitsch & Chintagunta, 2010;Gretz, 2010;Inceoglu & Park, 2011;Zhu & Iansiti, 2012;Kim, Prince & Qiu, 2014). In a reanalysis of the data from nine consumer electronic product categories, Stremersch et al (2007) compared the relative importance of the supply and demand effects.…”
Section: Attributes Of Ine Softwarementioning
confidence: 99%
“…They concluded that software availability typically followed hardware sales, while 'the reverse almost never happens' (Stremersch et al, 2007, p. 68). However, more recent studies focusing on specific categories have found evidence supporting the existence of demand effects in the markets for home video games (e.g., Corts & Lederman, 2009;Dubé, Hitsch & Chintagunta, 2010;Gretz, 2010;Zhu & Iansiti, 2012;Kim, Prince & Qiu, 2014) and DVD players (e.g., Inceoglu & Park, 2011).…”
Section: Attributes Of Ine Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…The interacting mechanism of indirect network effects can be represented explicitly by using two simultaneous equations: The purchase probability for the main product is expressed as a function of the availability of complementary goods, which, in turn, is specified as a function of the number of consumers using the main product. This technique has been used to examine indirect network effects for digital TVs (Gupta, Jain, and Sawhney, 1999), CD players (Le Nagard‐Assayag and Manceau, 2001), video recorders/DVD players (Inceoglu and Park, 2003; Karaca‐Mandic, 2004; Ohashi, 2003), and personal digital assistants (Nair, Chintagunta, and Dubé, 2004).…”
Section: Review Of the Diffusion‐modeling And The Utility‐based Approachmentioning
confidence: 99%